Lithuanian women in science: management facets - Dagytė, Ina (Business: Theory and Practice, 2008)
Though the proportion of women community in Lithuanian science and research and the interest in this phenomenon by representatives of different scientists are growing, yet the many unsolved or inefficiently solved problems, from thepoint of view of management, are signalled by certain characteristics of women scientists` social strata, efficiency of work,indexes of career development and acknowledgement processes. The article seeks to overview the experience of the Lithuanian women scientists within the period of 1990–2005 and identify the premises for the solution of the main managementproblems in the gender relations. The work uses the following methods of research: analysis, synthesis, observation, expertreview, comparison, structuring. The methods revealed the lack of the transformation management; the missing links inmanagement structures; the absence of legal acts to give assessment of the gender equality. The emerging and commendableself-management aspects and results in women society and within it in the women scientists` social strata are stressed. Theresults are manifested in the 3rd and 4th national congresses of Lithuanian women in 2000 and 2005.Article in Lithuanian.Lietuvos moterys moksle: vadybiniai aspektaiSantrauka. Nors moterų Lietuvos mokslininkų ir tyrėjų bendruomenėje daugėja, auga ir įvairių sričių tyrėjų susidomėjimas šia problematika, tačiau tam tikros moterų mokslininkių sociumo charakteristikos, veiklos rezultatyvumas, karjerą ir pripažinimą charakterizuojantys rodikliai signalizuoja apie įvairias neišspręstas ar nepakankamai efektyviai sprendžiamas problemas, patenkančias į vadybos mokslo problematikos lauką. Straipsnyje siekiama aktualizuoti Lietuvos mokslininkių bendruomenės raidos 1990–2005 m. m. patirtį ir išryškinti pozityvius bei negatyvius ypatumus, identifikuoti svarbiausias lyčių požiūriu balansuotinos Lietuvos mokslo vadybos problemas, aptarti identifikuotų problemų vadybinio sprendimo prielaidas. Darbe taikyti metodai: analizė, sintezė, stebėjimas, ekspertavimas, lyginimas, struktūravimas – padėjo atskleisti tikslingos šios srities transformacijų vadybos stygių, trūkstamas grandis vadybos organizavimo struktūroje, esminių pozityvių lyčių lygias galimybes įtvirtinančių teisės nuostatų realizavimo trukdžius. Akcentuojami besiformuojantys ir skatintini moterų bendruomenės, tarp jų ir moterų mokslininkių dalies, vadybos veiksniai ir rezultatai, išryškėja per III (2000) ir IV (2005) Lietuvos moterų suvažiavimus.Reišminiai žodžiai: mokslininkų bendruomenė; moterys mokslininkės; lygios galimybės; vadyba.First published online: 19 Mar 2008